A cidadania brasileira e a construção do negro pela retórica jurídica no Brasil - Oliveira, Rosiane Trabuco de (2022)
The notion of citizenship linked to equal rights has little to say about the effectiveness of guaranteeing such rights. It is necessary to go deep and verify on which foundations this notion is based. Thus, the purpose of this study is to analyze the legal process of construction of Brazilian citizenship, whose issues have an extremely negative impact on the black population, especially if we take the text of the Constitutions and related legal provisions, to compare with the contemporary moment. The intent is to demonstrate, through a documentary analysis – ethnography in archives and media – the conditions for the production of these legal statements in a given historical context, in dialogue with the subjects who produced them and imbued with moral values and configured in power relations. As the notion of citizenship is marked by an idea of a universal person supported by the Law, which, consequently, starts to exclude a portion of the population from social interaction and from the guarantee of behaving and circulating as a holder of rights, part of the discourses and practice Legal authorities have been placing blacks in limbo, considering them a “person” in a very particular way, having also been property. In this movement, the concept of device will be important in the present investigation, as it apprehends the link between living beings and the context in which they live, resulting in the knowledge-power process of constitutional statements and later theories (of men of science), the reverberate over the black population and, consequently, in the construction of a certain identity.